Plant growth regulators on sweet sorghum: physiological and nutritional value analysis - Macedo, Willian Rodrigues; Araújo, Diego Kitahara; Santos, Valdinei Moreira; Castro, Paulo Roberto de Camargo e; Fernandes, Gisele Machado (Comunicata Scientiae, 2017)
Sweet sorghum has gained attention in tropical and subtropical regions because of its potential as a bioenergy crop. The present research was carried out to evaluate the physiological, biochemical and nutritional characteristics of sweet sorghum submitted to six plant growth regulators (thiamethoxam, biostimulant mixture, gibberellic acid, chlormequat chloride, ethephon, and trinexapac-ethyl). The compounds were applied via foliar spraying in order to increase the productive potential of plants and reduce the carbohydrates sink strength by inflorescences. The experiment was conducted in pots and the following variables were evaluated: plant height, inflorescence dry matter, soluble solids content, shoot dry matter, crude protein, ashes, neutral detergent fiber and in vitro digestibility. It were observed the action of trinexapac-ethyl and ethephon to reduce the inflorescence dry matter, chlormequat chloride to increase the shoot dry matter, and trinexapac-ethyl to improve ashes content and reduce the neutral detergent fiber contents. These results indicate that chlormequat chloride and trinexapac-ethyl are effective in restricting the plant growth and increasing sorghum nutritional quality.